2001
DOI: 10.1042/bj3530621
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of elongation factor-2 kinase on serine 499 by cAMP-dependent protein kinase induces Ca2+/calmodulin-independent activity

Abstract: Elongation factor-2 kinase (eEF-2K) negatively regulates mRNA translation via the phosphorylation and inactivation of elongation factor-2 (eEF-2). We have shown previously that purified eEF-2K can be phosphorylated in vitro by cAMP-dependent protein kinase (PKA) and that this induces significant Ca2+/calmodulin (CaM)-independent eEF-2K activity [Redpath and Proud (1993) Biochem. J. 293, 31–34]. Furthermore, elevation of cAMP levels in adipocytes also increases the level of Ca2+/CaM-independent eEF-2K activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 14 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…It was previously reported that eEF2 phosphorylation suppresses eEF2 binding to the ribosome and inhibits polypeptide chain growth [44]. eEF2 phosphorylation is regulated by calcium concentrations, low pH value, activities of protein kinase A, and AMP-activated protein kinase [45][46][47], which leads to the inhibition of elongation. In our experiments, eEF2 phosphorylation was increased by unloading and was not regulated by the treatment with VX-745 inhibitor, whereas unloading-induced muscle atrophy was blocked in the HSVX group.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that eEF2 phosphorylation suppresses eEF2 binding to the ribosome and inhibits polypeptide chain growth [44]. eEF2 phosphorylation is regulated by calcium concentrations, low pH value, activities of protein kinase A, and AMP-activated protein kinase [45][46][47], which leads to the inhibition of elongation. In our experiments, eEF2 phosphorylation was increased by unloading and was not regulated by the treatment with VX-745 inhibitor, whereas unloading-induced muscle atrophy was blocked in the HSVX group.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples whereby cAMP elevations (Lawrence et al . 1997; Morgan and Beinlich 1997), protein kinase A activation (Diggle et al . 2001) or even stimulation of β‐adrenergic receptors (McLeod et al .…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence for an additional mechanism for controlling eEF2 kinase activity besides its activation by Ca 2+ /calmodulin was provided by the observation that cAMP‐dependent protein kinase (PKA) can phosphorylate eEF2 kinase [36,48]. This results in eEF2 kinase becoming partially independent of Ca 2+ /calmodulin for activity [48,49], i.e. it activates eEF2 kinase at low basal Ca 2+ levels.…”
Section: Regulation Of Eef2 Kinase By Pkamentioning
confidence: 99%
“…Diggle et al . [49] identified the site phosphorylated by PKA in rat eEF2 kinase as Ser499 (Ser500 is the human sequence), which lies outside the putative catalytic domain (Fig. 2) in a relatively poor consensus for phosphorylation by PKA.…”
Section: Regulation Of Eef2 Kinase By Pkamentioning
confidence: 99%